An Enhanced Mobile Phone Dialler Application for Blind and Visually Impaired People - Yousef, Rana Mohammad; Adwan, Omar; Abu-Leil, Murad (International Journal of Engineering and Technology, 2013)
This paper presents the development of a new mobile phone dialler application which is designed to help blind and visually impaired people make phone calls. The new mobile phone dialler application is developed as a windows phone application to facilitate entering information to touch screen mobile phones by blind people. This application is advantageous through its innovative concept, its simplicity and its availability at an affordable cost. Feedback from users showed that this new application is easy to use and solves many problems of voice recognition applications such as inaccuracy, slowness and interpretation of unusual voices. In addition, this application has increased the users’ ability to dial phone numbers more independently and less stressfully.